Prelacrimal Window Approach in the Management of Odontogenic Maxillary Sinusitis from Dental Foreign Body - Saikrishna Ananthapadmanabhan; Anthony Noor; Niranjan Sritharan (Hindawi Limited, 2022)
The floor of the maxillary sinus is partly formed by the alveolar process of the maxilla, and this anatomical relationship forms an interface for collaboration between rhinologists, maxillofacial and dental surgeons, and dentists. Odontogenic maxillary sinusitis (ODMS) occurs secondary to infectious processes of the maxillary molar and premolar teeth or following complications from dental procedures. Extruded dental foreign bodies within the sinus can cause chronic mucosal irritation leading to mucociliary dysfunction and sinogenic symptoms. Anteriorly placed foreign bodies are difficult to access via the conventional endoscopic maxillary antrostomy. Endoscopic approaches to access the anterior maxillary sinus involve extended resection of the medial maxillary wall, potentially with the removal of the inferior turbinate and nasolacrimal duct mobilisation. The prelacrimal window approach (PLWA) is a favourable modification that provides excellent visualisation of the maxillary sinus with minimal tissue resection and displacement. We describe the case of an extruded distobuccal 27 tooth root into the anterior maxillary sinus, presenting with acute sinusitis. The patient was successfully managed via a PLWA. This case represents the importance of recognition of ODMS with early referral to otorhinolaryngologists.